Facile gamma radiolytic synthesis of synergistic Co3O4-rGO nanocomposite: direct use in photocatalytic water splitting - Gupta, Bhavana; Melvin, Ambrose A.; Matthews, Tom; Dash, S.; Tyagi, A. K. (Materials Research Express, 2014)
Nanostructured Co3O4 was synthesized through a gamma (gamma)-radiolysis technique using alcoholic (iso-propanol) salt solutions of cobalt ions with and without suspended graphene oxide (GO) nanoparticles, respectively. Formation of Co3O4 accompanied with GO reduction takes place simultaneously (in situ) upon.-ray exposure carried out at a rate of 5.1 KGy h(-1). Reduction of GO and formation of Co3O4 were confirmed by XRD, Raman and UV-vis spectroscopy. XRD and HRTEM results supports the embedding of nano-crystalline Co3O4 in an amorphous matrix. Relatively larger crystallites of cobalt oxide obtained in the presence of rGO proved to be a decisive supporting material for the directional growth of Co3O4. Electrochemical characterization established the fact that rGO is indeed considered as a proficient medium for electrochemical electron transfer process. Photo-assisted H-2 generation studies using Co3O4 and Co3O4-rGO nano-composite yielded 3 and 30 mu mol h(-1) g(-1) of hydrogen (H-2) generation, respectively, supports the action of rGO as an electron trap.
Keywords: nano cobalt oxide; photocatalytic hydrogen production; Reduced graphene oxide

Poly (3,4-ethylenedioxythiophene) (PEDOT) and poly (3,4-ethylenedioxythiophene)-few walled carbon nanotube (PEDOT-FWCNT) nanocomposite based thin films for Schottky diode application - Gupta, Bhavana; Mehta, Minisha; Melvin, Ambrose A.; Kamalakannan, R.; Dash, Sitaram; Kamruddin, M.; Tyagi, A. K. (Materials Chemistry and Physics, 2014)
Transparent, conductive films of poly (3,4-ethylenedioxythiophene) (PEDOT) and poly (3,4-ethylenedioxythiophene)-few walled carbon nanotube (PEDOT-FWCNT) nanocomposite were synthesized by in-situ oxidative polymerization and investigated for their Schottky diode property. The prepared films were characterized by UV-Vis spectroscopy, thermal gravimetric analysis (TGA), surface resistivity, cyclic voltametery, scanning electron microscopy (SEM) and high resolution transmission electron microscopy (HRTEM). SEM reveals the formation of homogeneous and adhesive polymer films while HRTEM confirms the uniform wrapping of polymer chains around the nanotube walls for PEDOT-FWCNT film. Improved thermal stability, conductivity and charge storage property of PEDOT in the presence of FWCNT is observed. Among different compositions, 5 wt. % of FWCNT is found to be optimum with sheet resistance and transmittance of 500 Omega sq(-1) and 77%, respectively. Moreover, the electronic and junction properties of polymer films were studied and compared by fabricating sandwich type devices with a configuration of Al/PEDOT or PEDOT-FWCNT nanocomposite/indium tin oxide (ITO) coated glass. The measured current density-voltage characteristics show typical rectifying behavior for both configurations. However, enhanced rectification ratio and higher forward current density is observed in case of PEDOT-FWCNT based Schottky diode. Furthermore, reliability test depicts smaller hysteresis effect and better performance of PEDOT-FWCNT based diodes. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Composite materials; Electrical properties; Polymer; Thin films

Chemically grafted graphite nanosheets dispersed in poly(ethylene-glycol) by gamma-radiolysis for enhanced lubrication - Gupta, Bhavana; Panda, Kalpataru; Kumar, Niranjan; Melvin, Ambrose A.; Dash, Sitaram; Tyagi, Ashok Kumar (RSC Advances, 2015)
Graphite nanosheets (Gr-NS) dispersed in poly(ethylene-glycol) (PEG200) medium were subjected to various doses of gamma-irradiation. Hydroxyl functional groups present in PEG are chemically grafted through hydrogen bonding with hydroxyl, carbonyl and carboxylic groups of Gr-NS. The grafting process is driven by the generation of active radicals from solvent radiolysis. Chemical grafting was investigated using X-ray photoelectron spectroscopy (XPS) and Fourier transform infra-red (FTIR) spectroscopy. The results of spectroscopic studies revealed reduction in oxygen functionality of PEG-Gr-NS at higher doses of gamma-irradiation. The gamma-irradiation not only bridges the functionalities between PEG and PEG-Gr-NS but edge and basal plane defects in Gr-NS are further reduced as is evident from Raman analysis. The inter-planar sheet distance in Gr-NS is increased due to intercalated chemical grafting with PEG molecules. The chemical grafting between PEG and Gr-NS and reduction in defects enhance the tribological properties with a decrease of 26% and 32% for the friction coefficient and wear, respectively as compared to PEG alone. The lubrication mechanism is mediated through inter-planar weak forces when PEG is chemically grafted with Gr-NS. The electrostatic interaction of PEG with Gr-NS acts as a molecular bridge thus enhancing the sustainability of tribo-stress. Additionally, in the presence of functionalized PEG-Gr-NS tribo-contact conditions, evidence of deposited graphitic tribo-film was observed from micro-Raman spectroscopy inside the steel wear track. This film further enhanced lubrication mediated through low shear strength interlayer graphite sheets and therefore, antiwear properties were synergistically improved.

Facile gamma radiolytic methodology for TiO2-rGO synthesis: effect on photo-catalytic H-2 evolution - Gupta, Bhavana; Melvin, Ambrose A.; Matthews, Tom; Dhara, S.; Dash, Sitaram; Tyagi, A. K. (International Journal of Hydrogen Energy, 2015)
TiO2 (P25) decorated reduced graphene oxide (rGO) is synthesized by gamma-radiolytic technique using water-ethanol solvent medium. Visible light absorpdon was confirmed by UV-Visible spectroscopy. Photoluminescence (PL) study revealed a decline in electron-hole recombination rate signalled by a sharp fall in luminescence of TiO2. Under such scenario, electron transfer from TiO2 conduction band to the conjugated sheet becomes a preferred pathway in the presence of rGO, which is further confirmed by photocurrent measurement. TiO2 -rGO composite with 1 wt. % rGO was found to be the best composition in terms of visible light absorption, while retaining TiO2 crystallinity. Transmission electron microscopy and Raman spectroscopic studies confirmed the coating of rGO sheet with TiO2 nanoparticles. TiO2 -rGO was found to show about 150 times higher photocatalytic H-2 generation under 250 W UV-Visible light irradiation than pristine TiO2. In addition to this, TiO2 -rGO composite shows hydrogen production yield of 35 mu mol/h.g under visible light (lambda = 400 nm) irradiation. Thus gamma-radiolysis can be considered to be a viable technique, which helps in synthesizing photocatalytically active nanocomposite with high H-2 evolution rate. In the light of these interesting aspects, a detail investigation is carried out to study the effect of rGO concentration and illumination time on photocatalytic yield. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: gamma-radiolysis; H-2 production; Photocatalysis; Reduced graphene oxide; TiO2

M-Au/TiO2 (M = Ag, Pd, and Pt) nanophotocatalyst for overall solar water splitting: role of interfaces - Melvin, Ambrose A.; Illath, Kavya; Das, Tanmay; Raja, Thirumalaiswamy; Bhattacharyya, Somnath; Gopinath, Chinnakonda S. (Nanoscale, 2015)
M-Au/TiO2 (M = Ag, Pd, Pt) composites were prepared through a facile one-pot photodeposition synthesis and evaluated for solar water splitting (SWS) with and without a sacrificial agent. The M-Au combination exhibits a dominant role in augmenting the H2 generation activity by forming a bi-metallic system. Degussa P25 was used as a TiO2 substrate to photodeposit Au followed by Au + M (M = Ag/Pd/Pt). The SWS activity of the M-Au/TiO2 was determined through photocatalytic H-2 production in the presence of methanol as a sacrificial agent under one sun conditions with an AM1.5 filter. The highest H-2 yield was observed for Pt-0.5-Au-1/TiO2 and was around 1.3 +/- 0.07 mmol h(-1) g(-1), with an apparent quantum yield (AQY) of 6.4%. Pt-0.5-Au-1/TiO2 also demonstrated the same activity for 25 cycles of five hours each for 125 h. Critically, the same Pt-0.5-Au-1/TiO2 catalyst was active in overall SWS (OSWS) without any sacrificial agent, with an AQY = 0.8%. The amount of Au and/or Pt was varied to obtain the optimum composition and it was found that the Pt0.5-Au1/TiO2 composition exhibits the best activity. Detailed characterization by physico-chemical, spectral and microscopy measurements was carried out to obtain an in-depth understanding of the origin of the photocatalytic activity of Pt-0.5-Au-1/TiO2. These in-depth studies show that gold interacts predominantly with oxygen vacancies present on titania surfaces, and Pt preferentially interacts with gold for an effective electron-hole pair separation at Pt-Au interfaces and electron storage in metal particles. The Pt in Pt-0.5-Au-1/TiO2 is electronically and catalytically different from the Pt in Pt/TiO2 and it is predicted that the former suppresses the oxygen reduction reaction.

Effective noncovalent functionalization of poly(ethylene glycol) to reduced graphene oxidenanosheets through gamma-radiolysis for enhanced lubrication - Gupta, Bhavana; Kumar, Niranjan; Panda, Kalpataru; Melvin, Ambrose A.; Joshi, Shailesh; Dash, Sitaram; Tyagi, Ashok Kumar (Journal of Physical Chemistry C, 2016)
High-quality reduced graphene oxide (rGO) nanosheets (NSs) were synthesized by the oxidation of graphite followed by hydrazine treatment for the reduction of the oxygen functionalities. gamma-Radiolysis was then used for the functionalization of the rGO-NSs with poly(ethylene glycol) 200 (PEG200). The functionalization resulted in the intercalation of PEG200 molecules in rGO through hydrogen bonding between the hydroxyl groups of rGO and the oxygen atoms of PEG200 molecules. This resulted in an increase in the d spacing of the graphene sheets and a decrease in the defect density of the carbon network in the rGO. The friction coefficient and wear of sliding steel surfaces were reduced by 38% and 55%, respectively, when 0.03 mg mL(-1) PEG200-functionalized rGO dispersed in PEG200 was used. The lubrication properties can be described by bipolar interactions between PEG200 and rGO, leading to effective dispersion. Chemical analysis of wear particles showed decomposition of rGO into nanosized graphite domains, as exhibited by mechanical energy produced in tribo-contact. Moreover, these domains formed effective and stable tribofilms on the steel wear tracks that easily sheared under the action of contact stress. This significantly enhanced the antifriction and antiwear properties, resulting in improved oxidation resistance of PEG200 under the tribo-contact. It was found that, at high rGO concentrations, the lubrication efficiency decreased as a result of graphene-graphene intersheet collisions, producing mechanical energy and chemical defects at contact interfaces.

Molecular-Pillar-supported functionalized reduced graphene-oxide for energy efficient lubrication - Gupta, Bhavana; Kumar, Niranjan; Panda, Kalpataru; Melvin, Ambrose A.; Joshi, Shailesh; Dash, Sitaram (Advanced Materials Interfaces, 2016)
Molecular-pillar-supported basal plane of reduced graphene oxide (rGO) is fabricated by polymerizing polyaniline (PANI). In the presence of poly(ethylene glycol) (PEG200), the gamma-radiolysis is used for modifying the functionalization and improving the structural symmetry of PANI and PEG grafted rGO (PANI-PEG-g-rGO). The PANI is covalently and noncovalently grafted onto the surface of the graphene sheets. Carboxyl groups of rGO are linked to the nitrogen atoms in the PANI backbone and an accompanying noncovalent interaction between alkyl chains of grafted PANI and hydrooxylated rGO is formed. Raman and Fourier transform infra-red results confirm existence of stretching vibrations of benzenoid and quinonoid rings in PANI-PEG-g-rGO-functionalized composite, indicating grafting between PANI and rGO through pi-pi interaction. Furthermore, PEG-functionalization through hydrogen bonding with rGO is confirmed when hydroxyl group from the rGO combines with oxygen of PEG. X-ray photoelectron spectroscopy reveals significant increase in carbon, while loading PANI network with rGO followed by gamma-irradiation. Antifriction and antiwear properties of graphene nanocomposite are considerably enhanced to 68.4% and 48%, respectively, as compared to pristine PEG. The unique lubrication properties are explained by PEG functionalized molecular PANI-pillar structure across basal plane of rGO.

Is there any real effect of low dimensional morphologies towards light harvesting? a case study of Au-rGO-TiO2 nanocomposites - Melvin, Ambrose A.; Bharad, Pradnya A.; Illath, Kavya; Lawrence, Meenu P.; Gopinath, Chinnakonda S. (Chemistry Select, 2016)
Nanotube and nanosheet morphologies have been celebrated for their electron transport properties. Present work has been explored to exploit the same by combining 1D TiO2 nanotube (1D-TN) with 2D reduced graphene oxide (rGO) along with nano gold for visible light sensitization for photocatalytic H2 generation under one sun condition and visible light (λ≥ 400 nm). Vertical and horizontal electron transport in 1D-TN and rGO, respectively, is combined with the visible light absorption capability of Au nanoparticle. H2 yield (HY) varies between 100 and 655 µmol/g.h with an apparent quantum yield between 0.45 and 3.2 %, respectively, depending on Au/rGO/1D-TN preparation method and reaction conditions. It has been demonstrated that interfacial contact between rGO/1D-TN and Au is crucial for high photocatalytic HY. Preparation method influences charge utilization, and hence HY, to a large extent. Nonetheless, the maximum HY reported in the present work is just comparable to HY reported in literature with the most commonly found spherical morphology, and this leads to a question of, is there any real influence of 1D and/or 2D materials, particularly, towards light harvesting applications?

TiO2 modification by gold (Au) for photocatalytic hydrogen (H-2) production - Gupta, Bhavana; Melvin, Ambrose A.; Matthews, Tom; Dash, Sitaram; Tyagi, A. K. (Renewable & Sustainable Energy Reviews, 2016)
TiO2 is indeed one of the widely used semiconductors employed for photocatalytic hydrogen production. Most of its photocatalytic activity-is achieved in its crystalline form. However, its photocatalytic activity is limited to ultraviolet region. For making TiO2 visible light active; Au deposition is strongly recommended due to its surface plasmon feature. Au deposition enhances the photocatalytic activity of both crystalline and nanocrystalline TiO2. Efficiency of photocatalytic activity is controlled by shape and size of Au nanoparticle subsequently the synthetic methodology plays an important role. Herein, we furnish a brief description of TiO2-Au nanocomposite synthesis by different methods viz. sol-gel, photodeposition, deposition-precipitation simple reducing method and dispersion method. A discussion on physical properties of the resultant material is also provided. Three different types of mechanism has been described depending on the type of irradiation and form of TiO2 (crystalline and nanocrytalline). A comparative hydrogen production yield is also tabulated to get an idea about the best synthesis methodology and form of TiO2 for efficient photocatalysis. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Gold nanoparticle; Hydrogen generation; Nanocomposite; Photocatalysis; TiO2

TiO2/RGO composites: Its achievement and factors involved in hydrogen production - Gupta, Bhavana; Melvin, Ambrose A. (Renewable &sustainable energy reviews, 2017)
The immense potential shown by TiO2 to participate as a designer material resulting into a new class of high performing photocatalyst has acclaimed it to become an important player in the designing and synthesis of various solar harvesting materials. This role has further been explored by the introduction of graphene into TiO2 matrix. TiO2/reduced graphene oxide (TiO2/RGO) or TiO2/graphene (TiO2/GR) has shown its prospects or relevance to be considered as the next generation photocatalyst for hydrogen production by its reported values in terms of producing hydrogen gas. Hence, there is a requirement of having a detailed up to date write up on the work done in this area in terms of its synthetic procedures, properties and its effect on hydrogen production. Herein, we discuss the different methods involved in the synthesis of such highly efficient materials followed by a brief explanation on its structural and morphological properties. Furthermore, a comparative study on the recent developments in terms of hydrogen evolution efficiency along with a mechanistic approach is also described. Finally, the current challenge and possibility of the future development in this direction is emphasized.
Keywords: Au-tio2 Photocatalysts; Evolution; Generation; graphene; Hydrogen generation; Nanocomposite; Nitrogen-doped Tio2; Photocatalysis; Photocatalytic H-2 Production; Recent Progress; Reduced graphene oxide; TiO2; Tio2-graphene Nanocomposites; Visible-light Irradiation; Water